Beyond Confidentiality: Advocates’ Reporting Duties in the War Against Money Laundering - Adinda, Fadhel Arjuna; Rahmawati, Ema; Suparman, Eman; Sutiyoso, Bambang; Hamzah, Rosyidi; Woodward, John (Indonesian Journal of Advocacy and Legal Services, 2025)
The Principle of Recognizing Service Users (Prinsip Mengenali Pengguna Jasa, PMPJ), as outlined in Article 3 of Government Regulation No. 61 of 2021 concerning Amendments to Government Regulation No. 43 of 2015 on Whistleblowers in the Prevention and Eradication of Money Laundering Crimes, underscores the role of advocates as mandatory whistleblowers. This creates legal challenges regarding its implementation, resulting in a dialectical tension with the central argument that while PMPJ obligations are firmly grounded in normative legal frameworks, advocates—who are explicitly required to uphold these provisions—find no compelling legal basis for such duties in Law No. 18 of 2003 on Advocates (the Advocate Law). The principle of Lex Superior Derogat Legi Inferior further complicates this issue, as it suggests that the Advocate Law, being of a higher legal order, supersedes the obligations imposed by PMPJ. The primary objective of this study is to critically analyze the implementation of PMPJ, specifically focusing on the supporting and inhibiting factors in the context of preventing and combating money laundering crimes. The findings highlight that the failure to optimally implement PMPJ within the advocate profession is largely due to the unresolved legal dialectic surrounding the obligations of advocates. This issue has not been addressed in prior studies, representing a novel contribution of this research. Consequently, this study proposes the need for a reformulation of the Advocate Law, emphasizing the explicit inclusion of advocates' obligations regarding the implementation of PMPJ principles.